2021
DOI: 10.1259/dmfr.20200174
|View full text |Cite
|
Sign up to set email alerts
|

The association between carotid calcium on dental panoramic radiographs and coronary calcium score on chest computerized tomography

Abstract: Objectives: Coronary artery calcium measured by CT predicts future coronary events. Similarly, carotid artery calcium on dental panoramic radiographs has been associated with increased cardiovascular events. Pre-procedural assessment of candidates for valve replacement in our institution includes panoramic radiographs and chest tomography. We aimed to assess the association of carotid calcium on panoramic radiographs with coronary artery calcium on chest tomography. Methods: Paired pre-procedural panoramic rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The study by Carasso et al showed that the detection of CAC on PRs was correlated with high coronary artery calcium and tripled the probability of having a clinically significant coronary artery calcium score that warrants clinical evaluation [44]. Coronary artery calcium scoring is a widely available, specific, and readily reproducible means of assessing risk for coronary artery disease and cardiovascular events; a great assessment tool for asymptomatic individuals for planning preventive strategies.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Carasso et al showed that the detection of CAC on PRs was correlated with high coronary artery calcium and tripled the probability of having a clinically significant coronary artery calcium score that warrants clinical evaluation [44]. Coronary artery calcium scoring is a widely available, specific, and readily reproducible means of assessing risk for coronary artery disease and cardiovascular events; a great assessment tool for asymptomatic individuals for planning preventive strategies.…”
Section: Discussionmentioning
confidence: 99%
“…It involves the injection of contrast material and exposure to X-ray ionizing irradiation which, in addition to significant financial expenses, make this test inadequate for screening purposes. Panoramic dental X-rays may provide important information on carotid artery calcification [ 26 , 38 , 39 ]. They are performed routinely and the information on possible CAC can be retrieved without additional clinical test or procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Para a identificação de ateromas em radiografia panorâmica requer treinamento dos profissionais para este achado, e destaca que este exame complementar é uma ferramenta que pode sugerir diagnóstico importante de CAC. Além disso, em seu estudo, demonstrou que Cirurgiões-Dentistas que foram treinados por duas semanas para identificar os achados radiopacos obteve avanço significativo no diagnóstico de CAC, com aumento da precisão diagnóstica de 41,8% para 55,7% (p=0,02) 2021) referem eficácia de 50%, justificando que a radiografia panorâmica pode ser utilizada como ferramenta de triagem, mas não de diagnóstico de CAC 33,34 . O presente estudo corrobora e evidencia a necessidade de exames específicos, como a Ultrassonografia com Doppler de carótidas, para diagnóstico final de placas de ateroma diante da suspeita levantada através de radiografias panorâmicas.…”
Section: Contribuições E Limitações Da Radiografia Panorâmica No Diag...unclassified